Reaping Benefits of FDI and Reshaping Shanghai's Economic Landscape - World Bank (Washington, DC, 2013)
Foreign Direct Investment (FDI) has played a significant and positive role in driving economic growth and upgrading economic structure in Shanghai. The shift in the pattern of FDI over the last decade towards services has been particularly crucial. Given its importance, Shanghai municipal government may continue to devote efforts to attract FDI and have foreign funded enterprises help reshape Shanghai's economic landscape. The main importance of FDI to Shanghai lies less in its capital finance, and more in the extent to which foreign funded enterprises (FFEs) help move the city up the value chain and generate high-end jobs. In the post-financial crisis era, developing countries will take a much larger role in leading world growth while enhanced competition will accelerate the pace of service revolution. Possessing strong geographic advantages, Shanghai has the potential to become an international business and financial hub and to have the high-tech industries and services being the driving force of the growth. Shanghai has strong potential in reaping the benefits of FDI and reshaping its economic landscape in 12th Five Year Plan period. In terms of the three conditions to succeed good opportunity, favorable geographic location and harmonious society, Shanghai is already in a good position. This note seeks to provide insights to help the Shanghai government make the right decisions and trade-offs to better reap the benefits of FDI in the context of a changing global context.